The role of ICT in collective resilience in a time of crisis - John W. Cheng; Hitoshi Mitomo (International Telecommunications Society (ITS), 2015)
Studies find that in time of crisis such as natural disasters, in most cases, people in crowds are capable to remain calm and to help each other. Referred as 'collective resilience', this capability can increase a society's capacity to withstand crises and disasters. Therefore, for both academia and governments, it is important to understand the factors and mechanisms of collective resilience. Considering the increasingly important role of ICT in disasters, we anticipate that it can also contribute to collective resilience. However, currently few studies have explored the connections between these two concepts empirically. Thus, the aim of this study is to investigate the roles and effects of ICT in collective resilience in a time of crisis. This study uses the 2011 Great East Japan Earthquake as the case study. In particular, the large crowds of stranded commuters in Tokyo when the earthquake struck. Using a quantitative approach with 258 samples collected from a survey, the preliminarily results have shown the presence of collective resilience among the stranded commuters. For instance, most of them felt a sense of shared identity and interdependence with others. Moreover, the results have also revealed the two main roles of ICT in collective resilience. First, by providing information and advice on what to do, ICT information can keep people in a crowd to stay in the state of collective resilience together. The second role is to reduce the chance of mass panic or herd behaviour. This is because ICT information can increase a person's knowledge of the situation. Such knowledge can help them to make their own decisions rationally, thus reduce their dependence on others.
Keywords: 330